EXECUTIVE SUMMARY. AT THE FEDERAL LEVEL (Tufts Archival Research Center, 2007)
Executive Summary discussing tobacco-related issues at the federal and state levels. Summarizes the Environmental Protections Agency's Science Advisory Board's review of secondhand smoke risk assessment and policies on workplace smoking. Discusses local ordinances to ban smoking in restaurants.